Implementasi Fungsi Actuating Dalam Pembinaan Santri di Pondok Pesantren - Uswatun Niswah; Muhammad Rizal Setiawan (Jurusan Manajemen Dakwah, Fakultas Ilmu Dakwah dan Ilmu Komunikasi, UIN Syarif Hidayatulla, 2021)
This study aims to determine how the implementation of the actuatingfunction in fostering santri in Islamic boarding schools. The researchreported in this article employed a descriptive qualitative approach withinductive analysis techniques. Data was collected through observation,interview and documentation techniques. The results of the research indicatethat the